Elaboración de un plan de negocio para la creación de una empresa productora y comercializadora de mobiliario para alcoba, personalizado a través de una página web en la ciudad de Bogotá D.C. (2019)
An assessment is made about the potential consumers who Will be willing to obtain a bedroom furniture through a website; In addition, an evaluation id made of the possible suppliers that the organization will have, the necessary inputs for the elaboration of furniture in a period of time, the staff, the machines and the area where these products will be made; the form of constitution that is will have, the environmental impact that it may produce on the environment and the people around it. Finally a financial study is carried out, with which the viability of said project is determined; where the net present value (VPN) results in $804'930.400, the internal rate of return (TIR) has a value of 94% and a cost benefit ratio greater than 1.